Effective vocabulary learning tasks: Involvement Load Hypothesis versus Technique Feature Analysis. (February 2016) - Hu, Hsueh-chao Marcella; Nassaji, Hossein
Abstract: L2 vocabulary learning is a complex process involving not only understanding the meanings of words but also being able to retain, retrieve, and use them in production. To this end, learners need not only to pay deliberate attention to the target words but also have to deeply process the various aspects of the words to learn them effectively. This has been referred to as "elaborate processing." Two frameworks have been proposed to operationalize the construct of elaborate processing for L2 vocabulary learning: Involvement Load Hypothesis (ILH) and Technique Feature Analysis (TFA). However, the two frameworks vary in the ways they conceptualize elaborate learning and also in terms of their attentional components. The present study was designed to empirically compare these two frameworks and their predictability for effective L2 vocabulary learning tasks. Ninety-six adult EFL learners were divided into four groups, and were required to learn the meanings of 14 unknown words. Each group performed one of four vocabulary tasks ranked differently by the two frameworks. The results showed that the TFA had a better explanatory power in predicting vocabulary learning gains than the ILH. The implications of the findings for designing effective L2 vocabulary tasks will be discussed.